HUBUNGAN PENGETAHUAN PERAWAT DENGAN PENERAPAN UNIVERSAL PRECAUTION DALAM TINDAKAN PEMASANGANINFUS DIRUANG RAWAT INAP RSUD. DR. PIRNGADI KOTA MEDANTAHUN 2018 - BrSiregar, Sri Dewi (Jurnal Ilmiah Keperawatan, 2019)
Universal Precaution is an infection control action carried out by all health workers to reduce the risk of spreading infection. In the act of infusion there are 3 universal precautions, namely washing hands before the procedure of infusion, wearing gloves, and washing hands after infusion. The research design was descriptive correlation which aimed to find out whether there was a relationship between nurses’ knowledge and the application of Universal Precaution in the infusion procedure in the inpatient ward of Pringadi General Hospital, Medan City. The population in this study were all nurses in the inpatient ward of Pringadi General Hospital in Medan City as many as 52 nurses, taken by means of total sampling. Data analysis used bivariate analysis with Chi-Square test (P <0.05). The instrument used in this study is the nurse knowledge questionnaire about universal precaution and observation sheets for the application of universal precaution in the infusion procedure. The results showed that 51.9% of nurses in Pringadi Hospital Medan City applied Universal Precaution well in the infusion procedure. In the Chi-Square test it was found that there was a significant relationship between the knowledge variables on the application of Universal Precaution in the infusion procedure with a value of P = 0,000. The conclusion is that there is a relationship between nurses’ knowledge and the application of universal precaution in the act of infusion in RSUD. Dr. Pirngadi Medan City. Further research is recommended on the different application of Universal Precaution nursing in hospitals by adding other variables related to Universal Percaution.